The analysis of gender representations in selected South African Television Soap Operas - Fombang, Thelma Nih (My University, 2023)
Soap opera has become very popular recently. Some of the reasons for its popularity stems from how it mimics reality and its open-ended nature that has attracted a large audience and fan base. Therefore, the study analysed how gender was represented using three selected South African soap operas (Rhythm City, Scandal! and Generations: The Legacy). Alongside a codebook and 20 episodes per soap opera, a content analysis was used to meet the objectives which are; to analyse gender representation, identify dominant themes, identify gender-based roles and the trends found in all three soap operas. The study was based on the feminist and the hegemonic masculinity theory. For gender representation, results showed that there were males and females featured in all three soap operas but there was still a reluctance in queer portrayal. Queer characters were represented in just two of the soap operas and underrepresented with just two queer characters being the maximum. Furthermore, even though few queers were represented and found in two out of the three soap operas used in this study, queers were not represented as the “other”, which is a great improvement. However, there are still other stereotypes that come to the fore. Queers are represented as flamboyant and often in a secretive and once-off relationship. More women were portrayed in the workforce and both women and men were portrayed in skilled and unskilled jobs. Few men were represented in contra-stereotype jobs like cleaners and waiters. However, there is still a long way to go to achieve gender equality as women in the workplace were still portrayed in challenging situations like gender discrimination. Findings revealed that gender stereotypes still exist, however in a more subtle way. In the current study, soap operas have failed to portray a woman who can balance her professional career and family life, suggesting that a woman cannot have both. Men are still not represented in the domestic environment, like doing household chores. Also, even though there are more women like men in the workforce, the men have moved further up to demonstrate their superiority over women. They are into legal as well as illegal businesses that have put them steps ahead financially. Hence, women are still being dominated. Some of the prominent themes identified include motherhood, marriage, love and romance, crime, violence and family. The study recommended that content producers still need to work on producing content that is free of stereotypes and encourage gender equality and contents that are educative of what they hope the future should be. Female roles identified include motherhood, villainess, sex object, gold digger, and housewife. Also, men’s roles include father, villain, gold digger, womaniser and sex offender. Furthermore, the queers roles identified were emotionist and object of decoration. Common trends found in all three soap operas include the fact that most characters were between the ages of 24-29 and 30-45 years old and both genders doing skilled and unskilled jobs. The three soap operas were characterized by themes like motherhood, fatherhood, family, revenge and conflict, marriage, gender discrimination and violence. Similar roles in the findings on all three soap operas include mother, sex object, gold digger and career woman. For the men, roles include villain, model and spy and manipulator.
Thesis (M.A. (Media Studies)) -- University of Limpopo, 2023
Keywords: Gender; Representation; Soap opera; Gender-based roles; LGBT; Sex role; Gender expression; Television soap operas